Jury Commissioner Carl Hernandez's Retirement Dinner at Fresno County Plaza Ballroom - Watkins, Howard::::::::: (1988)
Municipal Court Judge Edward Sarkisian, Jr. speaking at lectern; Carl Hernandez, Fred Yamamoto, and Judges Mario Olmos and Robert Mardikian